G393 Work of breathing during CPAP and heated humidified high flow nasal cannula. (27th April 2016) - Shetty, S; Hickey, A; Rafferty, GF; Peacock, JL; Greenough, A
Abstract : Aims: Heated and humidified gas delivered at flow rates between 2–8 l/min via nasal cannulae (HHFNC) is increasingly being used as an alternative to continuous positive airway pressure (CPAP). Studies comparing the work of breathing (WOB) on CPAP and HHFNC, however, have given conflicting results. Our aim was to determine in infants with evolving or established bronchopulmonary dysplasia (BPD), whether CPAP compared to HHFNC reduced the WOB and thoraco-abdominal asynchrony (TAA) and improved oxygen saturation (SaO2 ). Methods: Infants born at less than 32 weeks of gestation and who were on CPAP and more than 40% oxygen at or beyond two weeks of age were eligible for this study. Infants were studied on two consecutive days. They were randomised on the first day to CPAP or HHFNC each for two hours and on the second day the order in which the modes was studied was reversed. The WOB was assessed by measuring the pressure time product using a dual pressure transducer tipped catheter and TAA by respiratory inductance plethysmography. WOB, TAA and SaO2 were assessed during the last five minutes at the end of each two hour period. The results from the two study periods were meaned. Results: Twenty infants with a median gestational age of 28 (range 24–32) weeks and birth weight of 888 (range 512–1500) grams were studied at a median postconceptional age of 31 (range 28–39) weeks. There were no significant differences in the results (data expressed as median, range) of the physiological measurements (see Table 1 ). Conclusion: In infants with evolving or established BPD, CPAP compared to HHFNC offered no significant advantage with regard to the WOB, degree of asynchrony or oxygen saturation.